(untitled) (INNOVATIVE ECONOMY, 2020)
Sharkovska S.O. INCREASING THE ECONOMIC EFFICIENCY OF SUNFLOWER SEEDS PRODUCTION IN AGRICULTURAL ENTERPRISES OF THE KYIV REGION Purpose. The aim of the article is the estimation of the production of sunflower seeds at agricultural enterprises of the Kyiv region and substantiation of directions for increasing its efficiency. Methodology of research. The following methods are used in conducting the research: monographic (for the comprehensive and in-depth study of individual phenomena, processes, and the identification of causal relationships of their development), systemic (consists in researching certain objects as complex systems), economics and mathematics (enabled to establish quantitative influence of separate factors on the researched result), statistical (when working with statistical information and outputting analytical expressions. Findings. It has been established that the production of sunflower in Ukraine in recent years has become increasingly developed and profitable, subject to certain features being taken into account. It is determined that one of the ways to increase the efficiency of sunflower production is the introduction of modern technologies for its cultivation and, in particular, the use of resource-saving technologies and the achievement of the growth of yields is very important. It was revealed that increasing the level of efficiency of sunflower seed market is a versatile problem. Its solution requires a comprehensive solution to the economic, organizational and agricultural issues that will enable a significant increase in the production of sunflower seeds. Originality. Theoretical, methodological and practical recommendations for increasing the economic efficiency of sunflower seeds production at agricultural enterprises of the Kyiv region are substantiated. Practical value. The obtained results of the research are the main preconditions for solving the problems for increasing the efficiency of sunflower seeds production. Key words: sunflower; production; efficiency; agricultural enterprises; profitability; profit; production.